Simulation of a remote runway solution for a congested airport: Mexico City Airport. (8th November 2019) - Mota, Miguel Mujica; Scala, Paolo
The airport of Mexico City has been declared saturated for most of the day. For that reason, the Mexican government announced a couple of years ago the construction of a completely new one which is supposed to be operative in 2020 in its first phase. However, the technical issues and the economic downturn in the country jeopardise the project; for that reason, it is important to have alternatives that allow investing in a progressive fashion so that the investments are not lost or end up in useless infrastructure like the ones that have taken place in other parts of the world. The current work presents a simulation-based study of the alternative of using one of the runways of the new airport in a remote fashion in case the original project is delayed or even cancelled. The results indicate that the proposed infrastructure alleviates the congestion problem in the current airport, and at the same time allows the traffic growth with performance indicators similar to airports that have remote runways as in the case of Schiphol in The Netherlands.